Plasma Antithrombin III and Factor VIII Antigen in Relation to Angiographic Findings, Angina and Blood Groups in Middle-Aged Men - Stormorken, Helge; Erikssen, Jan (Thrombosis and Haemostasis, 1977)
In a prospective study on latent coronary heart disease (CHD) in 2,014 presumably healthy men aged 40–59 years, 115 had strong clinical evidence of CHD never diagnosed nor suspected prior to the survey. Coronary angiography was performed in 105 of these. In 80 of them – whereof 57 were angiopositive and 23 angionegative – AT III and factor VIII Ag were assayed as well as in 35 normals from the same material. The results showed that:1. AT III was significantly lower in the angiopositive than in the normal controls.2. Subdivision of the angiopositive into those with and those without angina pectoris revealed significantly lower level of AT III in the former.3. Within blood group A only did the angiopositive subjects have significantly lower AT III than the remaining subjects in the group, and this was entirely due to the low values in those with angina pectoris.4. Blood group 0 individuals had significantly lower factor VIII Ag level than all other blood groups.The significance of these findings for the possible relation to development of atheromatosis is briefly discussed.